Professional Preparation of Masters for the Development of Projects of Corporate Socially Responsible Entrepreneurship in the Field of Education (Foreign Practices): Array - Bila, Olena (Journal of Danubian Studies and Research, 2020)
The article reveals modern approaches to the implementation of projects of corporate socially responsible entrepreneurship in educational institutions. The author analyzes the main trends of university training for masters in the development and implementation of strategies for corporate socially responsible entrepreneurship in the conditions of foreign Universities. The article presents methodological guidelines for the organization of the educational process of socially responsible education managers.